ARTIFICIAL INTELLIGENCE AND LANGUAGE TEACHING - Kadyrkulova U. K.; Tilekmatova A.; Usenalieva S. (Vestnik Issyk-Kulʹskogo universiteta)
The authors of the article address the topic of using the capabilities of artificial intelligence in language teaching. The system of education and science today is faced with the active use of artificial intelligence by students and learners. The authors try to analyze the advantages and disadvantages of using artificial intelligence. On the one hand, the ability to use the achievements of science and technology is welcomed, on the other hand - the use of ready answers weans students from the ability to think, compose, create, memorize. Artificial intelligence is a good assistant for a human being, but can it completely replace a teacher? The article discusses the advantages and disadvantages of using artificial intelligence in language teaching. The authors conclude that it is necessary to skillfully combine traditional teaching and artificial intelligence capabilities, which will lead to effective results.